Liza's second chance - Jebber, Molly (Jebber, Molly. Amish Charm Bakery series., 2018)
For Liza Schrock, the bakery her late husband bought was an unexpected haven from their unhappy arranged marriage. Now she's perfectly content to cook up mouth-watering delights for her hometown, give to those alone or in trouble - and remain happily unwed. And though she's willing to give handsome, newly-arrived widower Jacob Graber all the help he desperately needs, she is sure they can stay just friends . . . But as Liza also tries to aid Jacob's troubled teenage daughter, she starts caring far too much for his gentle ways and steadfast hopes. And when a wrenching secret she must keep comes between them, can Liza find the faith to risk opening her heart again - and reach for one more chance at real love?